Efficacy of a Poly-L-Glutamic acid-gemcitabine conjugate in tumor-bearing mice - Kiew, L.V.; Cheong, S.K.; Ramli, E.; Sidik, K.; Lim, T.M.; Chung, L.Y. (2012)
Strategy, Management and Health Policy Enabling Technology, Genomics, Proteomics Preclinical Research Preclinical Development Toxicology, Formulation Drug Delivery, Pharmacokinetics Clinical Development Phases I-III Regulatory, Quality, Manufacturing Postmarketing Phase IV This study assessed the in vivo antitumor efficacy of a polypeptide-based poly-L-glutamic acid-gemcitabine conjugate (PG-G). PG-G was synthesized by conjugating gemcitabine to poly-L-glutamic acid by a carbodiimide reaction. PG-G was evaluated for its in vivo antitumor efficacy and toxicity using 4T1 murine breast tumor-bearing mice. The antitumor effects of PG-G were superior to those of unconjugated gemcitabine in both single and four-consecutive dosing studies. Tumor regression was observed within 1 day after PG-G administration and continued for 45 days. Thereafter, tumors grew at a slower rate compared with the unconjugated gemcitabine treatment group and other control groups. The main toxicity observed from the Berlin test was an apparent reversible weight loss of 1012. The unconjugated gemcitabine treatment group also demonstrated a similar, but reduced, weight loss trend. The present study demonstrates that the PG-G formulation exhibits a significant antitumor activity in the aspects of tumor growth inhibition and shrinkage that is more robust than the parent drug and other control groups. Thus, the PG-G dose regimen may be optimized to minimize side effects and render it a potential anticancer therapeutic.